2012
DOI: 10.1177/0890334412459903
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Fortification with Differing Amounts of Fortifier and Its Association with Growth and Metabolic Responses in Preterm Infants

Abstract: We demonstrated that blind fortification of HM, even with higher amounts than recommended by manufacturers, did not cause any measured adverse effects on the metabolic response of preterm infants. Anthropometric measurements (except head circumference) were not different between the different dosages of fortification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
1
21
0
3
Order By: Relevance
“…Hypercalcaemia may be a risk and testing serum calcium and serum phosphorous more regularly should be considered. 8 Kanmaz et al 20 ( Table 2) reported two levels of blind fortification (moderate and aggressive) compared to standard fortification in a group of ELBW and VLBW infants with a gestational age of about 28 weeks. Moderate and aggressive fortification led to non-significant increases in weight and length, but head circumference increased significantly.…”
Section: Super Fortificationmentioning
confidence: 99%
See 4 more Smart Citations
“…Hypercalcaemia may be a risk and testing serum calcium and serum phosphorous more regularly should be considered. 8 Kanmaz et al 20 ( Table 2) reported two levels of blind fortification (moderate and aggressive) compared to standard fortification in a group of ELBW and VLBW infants with a gestational age of about 28 weeks. Moderate and aggressive fortification led to non-significant increases in weight and length, but head circumference increased significantly.…”
Section: Super Fortificationmentioning
confidence: 99%
“…According to a Cochrane review 20 on multicomponent fortification of human milk, it does not appear to be associated with adverse effects, even though the limited total sample size and missing data threaten the generalisability. As expected, increased enteral protein intake may increase blood urea levels and decrease blood pH levels, but the clinical significance thereof is unclear.…”
Section: Adverse Effects Of Fortificationmentioning
confidence: 99%
See 3 more Smart Citations